Direct agglutination test: Evolution and significance as a simple and safe alternative to tissue aspiration procedures in the diagnosis of visceral leishmaniasis. - Abdallah El Harith; Hussam Ali Osman; Durria Mansour; Saul J Semiao-Santos; Elfadil Abass (PLoS ONE, 2025)
Although tissue aspiration procedures (TAPs) are considered the gold standard for visceral leishmaniasis (VL) diagnosis, they often fail to detect disease progression before the amastigote-demonstrable phase. To overcome this limitation, a primary direct agglutination test (DAT) was developed using intact Leishmania donovani promastigotes initially treated with trypsin as the antigen. To enhance the exposure of specific epitopes on the promastigote surface and antibody-binding sites, alternative proteolytic agents were evaluated and incorporated into antigen processing and test execution. This approach led to significant or complete inhibition of agglutination in most known cross-reacting disorders. The LQ-DAT consistently demonstrated highly reproducible results across diverse geographical regions, regardless of the L. donovani sub-species or strain. To facilitate routine implementation and local production, the LQ-DAT processing know-how was disseminated to all major VL-endemic areas. Sensitivities comparable to TAP outcomes were demonstrated in 2,224 of 2,697 VL cases successfully diagnosed and treated over 35 years of routine, epidemic, and outbreak evaluations. Notably, 473 (17.5%) of these cases were symptomatic, with TAP-negative but LQ-DAT-positive results, and responded favorably (98.0%-100%) to specific treatment. Given the lower sensitivity also demonstrated by LQ-DAT, TAP does not meet the criteria for classification as the gold-standard VL diagnostic. Consequently, a positive response to specific anti-leishmanial treatment is recommended as a benchmark for diagnostic reliability. Beyond its advantage in detecting VL at earlier stages compared to TAP, the improved LQ-DAT described here also exhibited feasibility and stability required for local production in low-resource settings.